The Influence of Variety and Climatic Year on the Phenology of Blueberry Grown in the Banat Area, Romania - Sina Cosmulescu; Maria Marina Merca Laies; Veronica Sărățeanu (Agronomy, 2022)
This paper’s aim was to investigate the influence of variety and the climatic year on vegetation phenophases in blueberries grown in southwest Romania, the Banat region. This study was carried out during the growing season of 2020–2022 in a blueberry plantation, for ‘Duke’, ‘Hannah’s Choice’ and ‘Elliott’ varieties. In the study, phenological traits were recorded using the BBCH phenological scale and the observation of phenotypic data was recorded as in Julian days. Thus, it is found that the duration of each phenophase characterized each variety. The calendar periods for the onset of vegetation and the duration of spring phenological development stages in varieties have differed from year to year and depended on weather conditions. In the case of the phenological stage, depending on variety, the maximum amplitude was recorded for BBCH 87 stage (75% blue fruits) of 51 days, and the minimum amplitude, of 25 days, for BBCH 51 stage (bud swell) and BBCH 59 (late pink bud). The coefficient of variation, depending on climatic year, for generative phenophases, had values between 6.5% (BBCH 67-petal fall) and 21.1% (BBCH 51-bud swell). It was found that the variety and the climatic year influence the development of vegetation phenophases. The results indicate that blueberry cultivars have demonstrated a high degree of phenotypic plasticity to respond to gradual changes in environmental conditions and are important for the evaluation of cultivar cultivation prospects in the studied area.